2003
DOI: 10.1038/sj.bjc.6601152
|View full text |Cite
|
Sign up to set email alerts
|

Effects of imatinib mesylate (STI571, Glivec) on the pharmacokinetics of simvastatin, a cytochrome P450 3A4 substrate, in patients with chronic myeloid leukaemia

Abstract: The inhibition by imatinib of the cytochrome P450 3A4 isoenzyme may reduce the CYP3A4-mediated metabolic clearance of clinically important coadministered drugs. The main purpose of this study was to evaluate the effect of the coadministration of imatinib on the pharmacokinetics of simvastatin, a probe CYP3A4 substrate. In total, 20 patients with chronic myeloid leukaemia received an oral dose of 40 mg of simvastatin on study day 1. On study days 2 -7, each patient received 400 mg of imatinib once daily orally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(98 citation statements)
references
References 22 publications
2
95
1
Order By: Relevance
“…A recent study suggested that the inhibition by imatinib of the P450 3A4 isoenzyme might reduce the CYP3A4-meidated metabolic clearance of clinically important co-administered drugs (O'Brien et al 2003). CYP3A is a member of the superfamily that has a capacity of metabolizing immunosuppressive agents, including CyA and tacrolimus (Hesselink et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that the inhibition by imatinib of the P450 3A4 isoenzyme might reduce the CYP3A4-meidated metabolic clearance of clinically important co-administered drugs (O'Brien et al 2003). CYP3A is a member of the superfamily that has a capacity of metabolizing immunosuppressive agents, including CyA and tacrolimus (Hesselink et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may underlie this, including adherence to therapy, variability in the metabolism of imatinib by the CYP enzyme system and drug-drug interactions. 18,[19][20][21][22][23] Although a plasma trough imatinib concentration of 1000 ng/ ml or above has been associated with achievement of cytogenetic and molecular responses in CML, 15,16 there is variability in the test, and clinical parameters can guide medical management of most patients. Measurement of plasma levels may be useful in some specific scenarios, such as where poor compliance is suspected.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…15 The reasons for these variations in imatinib plasma concentrations are not fully defined, but may include: (i) incomplete adherence with the therapeutic regimen; (ii) patient demographic factors such as sex, age, body weight and body surface area (BSA); (iii) differential absorption from the gastrointestinal tract; (iv) intrinsic variability in metabolizing enzyme activity (CYP3A4) and enzymatic drug-drug interactions and (v) differential binding of imatinib by a 1 -acid glycoprotein in the plasma. [18][19][20][21][22][23] Incomplete adherence with the therapeutic regimen With the advent of targeted, oral anticancer agents prescribed as chronic therapy, adherence is becoming a major concern. 24 For patients with life-threatening diseases, X95% adherence is generally considered the goal.…”
Section: Factors Affecting Imatinib Plasma Pk Exposurementioning
confidence: 99%
“…The cytochrome P450 (CYP) system is involved in the oxidative metabolism of imatinib, the major reaction being catalyzed by CYP3A4/5 (O'Brien, et al 2003b;Peng, et al 2005;van Erp, et al 2007). Indeed, the main metabolite of imatinib, the N-desmethyl derivative CGP74588, is primarily formed in the liver by cytochrome CYP3A4, whereas a number of other enzymes such as CYP1A2, CYP2D6, CYP2C9, and CYP2C19 are involved in the formation of minor metabolites (O'Brien, et al 2003b;van Erp, et al 2007). CGP74588 represents approximately 20% of the parent drug plasma level in patients, and it has similar biological activity but a longer terminal half-life (85-95 h) than imatinib, as measured after discontinuation of therapy Table 5.…”
Section: Pharmacokinetics Of Imatinibmentioning
confidence: 99%